2020
DOI: 10.1111/apa.15260
|View full text |Cite
|
Sign up to set email alerts
|

Non‐immune hydrops fetalis was rare in Sweden during 1997‐2015, but cases were associated with complications and poor prognosis

Abstract: Hydrops fetalis is a serious, life-threatening condition caused by excessive and abnormal fluid accumulation in the foetus. It is commonly diagnosed based on the demonstration of abnormal fluid collection in at least two foetal compartments. 1 Historically, hydrops fetalis was primarily observed in association with Rhesus incompatibility. This aetiology is now rare owing to routine immunisation of Rhesusnegative mothers, and today most cases of foetal hydrops can be described as non-immune hydrops fetalis (NIH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 26 publications
2
28
0
Order By: Relevance
“…3,32 The overall outcome for liveborn infants is poor, with the first-year survival rate at approximately 50%. 5,6,27,30,32 In our case, even if the hydrothorax was present between at least 21 and 26 gestational weeks, the newborn showed no respiratory complications and good perinatal outcomes. At the last medical control at 10 months of age, the infant still presented no cardiorespiratory disorders.…”
Section: Discussionmentioning
confidence: 45%
See 3 more Smart Citations
“…3,32 The overall outcome for liveborn infants is poor, with the first-year survival rate at approximately 50%. 5,6,27,30,32 In our case, even if the hydrothorax was present between at least 21 and 26 gestational weeks, the newborn showed no respiratory complications and good perinatal outcomes. At the last medical control at 10 months of age, the infant still presented no cardiorespiratory disorders.…”
Section: Discussionmentioning
confidence: 45%
“…Due to difficulty in diagnosis and potential early spontaneous pregnancy termination, the incidence of hydrops fetalis varies considerably in different studies, ranging from 1.6 to 5.9 per 10,000 pregnancies. 5 , 6 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These masses may obstruct venous return and complications such as fetal hydrops, which can cause fetal death in severe cases. Studies have shown that the survival rate of the fetus with edema is only 3% [ 5 ], and is associated with several obstetric complications, such as preterm delivery [ 6 ] and high stillbirth rate [ 7 ]. Therefore, carrying out the prediction and early diagnosis of the risk of developing fetal hydrops caused by CLM and implementing preventive interventions and treatment measures for high-risk groups are essential to reduce the incidence of fetal hydrops and improve the quality of prognosis of the child.…”
Section: Introductionmentioning
confidence: 99%